Freudian Approach to Psychological Condition and Behavior Through the Characters of Mr and Mrs White - Febriandy, Agustio; Rahmawati, Irma (Universitas Lampung, 2024)
This study delves into the psychological underpinnings of W.W. Jacobs' 1902 short story